Relationship between visual motor integration skills and cursive hand writing among Indian children - DR.U. GANAPATHY SANKAR (International Journal of Pharma and Bio Sciences, 2018)
To identify relationship between Cursive handwriting speed, legibility and visual motor integration skills among Indian Children. This is quantitative research –correlation design. Five hundred children were recruited from normal school in west mambalam, Tamilnadu through convenient sampling. Evaluation Tool for Children Handwriting (ETCH-C) and Development test of Visual Motor Integration (VMI) was used to identify children handwriting speed, legibility and visual motor integration skills. Results found that there was positive correlation between legibility components of ETCH-C and principal test of VMI (r= 0.84), supplemental test of visual perception (r=0.87), supplemental test of motor coordination (r=0.81). Hand writing speed of ETCH-C was positively correlated with principal test of VMI (r= 0.82), supplemental test of visual perception (r=0.75), supplemental test of motor coordination(r=0.84). The Author concludes that there is strong positive relationship between visual motor integration skills and cursive handwriting legibility and speed of children. It shows that VMI skills increase, cursive handwriting speed and legibility of children also increases.